2019
DOI: 10.1111/jdv.15819
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy and dermoscopy aid in evaluating repigmentation within or adjacent to lentigo maligna melanoma surgical scars

Abstract: Background: Determining whether repigmentation within or adjacent to lentigo maligna or lentigo maligna melanoma (LM/LMM) scars represents recurrence of melanoma is challenging. The use of reflectance confocal microscopy (RCM) and dermoscopy may aid in differentiating true melanoma recurrence from other causes of repigmentation.Objectives: To describe the characteristics of repigmentation within or adjacent to LM/LMM scars observable on RCM and dermoscopy. Methods:We retrospectively analysed patients who prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…After re‐reviewing the images, no RCM evidence of residual LM/LMM was found which could be explained by the presence of focal residual LM/LMM on final pathology. The present study also complements the current literature on the feasibility of RCM evaluation of previously biopsied/surgically treated tissue …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…After re‐reviewing the images, no RCM evidence of residual LM/LMM was found which could be explained by the presence of focal residual LM/LMM on final pathology. The present study also complements the current literature on the feasibility of RCM evaluation of previously biopsied/surgically treated tissue …”
Section: Discussionsupporting
confidence: 66%
“…We found that RCM was associated with a diagnostic accuracy of 78.6%, a sensitivity of 90.9% and a specificity of 33.3% for the detection of residual LM/LMM, when compared to histopathology. With a sensitivity of >90%, RCM has the potential to accurately locate the area of residual LM/LMM . Nevertheless, specificity in our study was relatively low (<50%).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Reflectance confocal microscopy, biomarkers, liquid biopsies and the recognition of circulating tumour cells and cell-free DNAs/RNAs are promising methods for the early detection of recurrences which are still at the cellular level and which cannot be detected by conventional screening tools. [35][36][37] In conclusion after onset of metastases, the course of the disease is very similar in ER and LR, when early recurrence is defined up to 10 years and late recurrence after 10 years. Whereas immunological control may contribute to late onset of metastasis, once metastasis occurred it seems that the tumour escapes from immunological control.…”
Section: Discussionmentioning
confidence: 99%
“…Further examples are light reflectance spectroscopy [1], optical coherence tomography (OCT) [2], high wavenumber spectra (so called Raman spectrometry) [3] and video-rate multi-colored structured illumination microscopy [4,5], and also MRT-imaging with instruments that are in routine or research use for humans. An overview concerning alternative techniques to frozen sections is given by Eissa et al last year [6].…”
mentioning
confidence: 99%